Promoting diversity in the esl classroom : An approach to learner training / Suchithra Nair - Nair, Suchithra (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
The ways in which students characteristically acquire, retain and retrieve information are collectively termed as the students' learning style. This exploratory research project was conducted to foster awareness of the diverse learning styles that co-exist in a language classroom. This study examines the possibility of using learning styles as content and contextual theme for the first unit in a proficiency class. At the heart of this study is the desire to help a group of Preparatory English Course (PEC) students discover their language learning styles and to suggest appropriate strategies to deal with their uniqueness. Research has proven that the integration of learning styles in the ESL classroom not only facilitates academic success but also establishes good foundation to teach learning strategies (Reid, 1996). Within this context, an instructional unit was designed and implemented. This paper describes how the unit was used in a PEC classroom comprising 30 Part I Engineering students. What conclusions can we make? Abetter understanding of learning styles can be beneficial to both lecturers and students. The lecturers should be aware of the diversity in learning styles present in the language classroom and adjust instruction accordingly. Just as importantly, students can benefit by learning about their personal learning styles and becoming active participants in the language classrooms.